ANALISIS KEAMANAN PANGAN IKAN LAYANG (Decapterus spp) ASAP DI DESA LAMOMEA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Tamtama, Ary; Dwi Pratiwi, Pepin (Fakultas Pertanian Universitas Muhammadiyah kendari, 2023)
Smoked fish is one of the processed fishery products which is quite popular with the community, one of which is in Lamomea Village, Konda District, South Konawe Regency. The smoked product is generally liked by the public because of its distinctive savory taste, delicious aroma, affordable price, and is available at any time. This research aims to determine the process of making smoked scad fish (Decapterus spp), the proximate levels of scad fish (Decapterus spp) and to determine the total microbes in smoked scad fish (Decapterus spp). This study used a completely randomized design to look at the levels of proximate, total microbes and formalin in smoked scad fish (Decapterus spp) in sample A and sample B to look at the process of making smoked scad fish (Decapterus spp), levels of proximate and total microbes in smoked scad fish (Decapterus spp). Decapterus spp). The results show that the proximate content, namely water content, shows results in sample A with a value of 56.24 ± 0.91, while for sample B with a value of 41.26 ± 1.15, protein content in sample A with a value of 30.13 ± 0.56 and sample B 43.09 ± 2.33 fat content in sample A with a value of 4.08 ± 0.06 and sample B with a value of 4.08 ± 0.05 and ash content with a value of 7.97 ± 0.36 and in sample B with a value of 8.28 ± 0.87, the results of proximate levels in smoked scad fish (Decapterus spp) are in accordance with the SNI 2725:2013 standard. The total microbial results for smoked scad fish (Decapterus spp) in sample A showed a result of 9.3 × 103 col/g while for sample B the value was 2.8 × 103 col/g. This value shows that the average total plate number in smoked fish samples A and B are still in accordance with the requirements of SNI 2332.3: 2015. The results of formalin levels in smoked scad fish (Decapterus spp) obtained from quantitative analysis of formalin content in smoked scad fish were sample A 5,384 ppm and sample B 3,748 ppm.